Analysis of Financial Statements to Measure the Level of Health in The LPD of Pecatu Village, South Kuta, Badung - N W Indah Leonita; I N Sugiarta; Paulus Subiyanto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The Village Credit Institution (LPD) is an institution that operates in the financial sector belonging to the village which is developing and providing benefits both in terms of social, economic and cultural aspects to its citizens, so it is necessary to improve performance and preserve its existence. As a part of the traditional village unit in Bali, the LPD has the function of collecting funds and distributing credit and loans to the community. The level of soundness of the LPD shows the institution's ability to utilize its assets productively and efficiently and can manage the continuity of the business that is run effectively, so that it will encourage the continuity of the business. This study aims to measure the level of financial health using the CAMEL method on Village Credit Institution (LPD) of Pecatu Village, South Kuta, Badung in the period 2018 to 2020. Qualitative descriptive analysis is used to interpret the results of the calculation of financial ratios consisting of aspects of Capital, Assets, Management, Earning, and Liquidity. The result of this is the combined scores of all aspects obtained for 2018 is 79,37%, in 2019 is 80,77%, and in 2020 is 65,90%. Therefore it can be concluded that for 2018 and 2019 the financial health level of the LPD of Pecatu Village is in a fairly healthy condition, while in 2020 the financial health level of the LPD of Pecatu Village is in an unhealthy condition